Green polymer electrolytes of chitosan doped with erbium triflate - Alves, Raquel Diana Carneiro (2018)
Green Solid Polymer Electrolytes (SPEs) containing Er3+ ions have been prepared by solvent casting process. Chitosan was used as host polymer and the trivalent cations, as erbium triflate (Er(CF3SO3)3), have been incorporated into the matrix. The thermogravimetric analysis were used to evaluate the thermal stability of the electrolytes and the minimum onset decomposition temperature was 139ºC. Morphology analysis have revealed the predominant amorphous character of the analysed samples. Complex Impedance Spectroscopy was used to evaluate the conductivity of the samples as a function of temperature. The most conducting electrolyte had higher amount of glycerol (CS(ErTrif)0.05Gly0.70) and displayed 2.06x10-5 and 5.91x10-4 S cm-1 at 30ºC and 90ºC, respectively. This SPE was chosen to assemble a small electrochromic device with glass/ITO/PB/CS(ErTrif)0.05Gly0.70/CeO2-TiO2/ITO/glass configuration, which behaviour was studied by cyclic voltammetry and transmittance.